2008
DOI: 10.1249/mss.0b013e31817c92c0
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Testing to Estimate Survival in Pulmonary Hypertension

Abstract: : CPET parameters predict survival in PH patients and add marginally to the prognostic value of the 6MWD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
105
7
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 23 publications
14
105
7
10
Order By: Relevance
“…This was also demonstrable in a meta-analysis of the many treatment trials in PAH [141]. It retains significance in multivariate analyses even when other strong predictors are included such as patient demographics [127,140], baseline haemodynamics from right heart catheterisation or CMR [140,142,143], CPET variables [92,113] and presence of pericardial effusion [127]. Absolute values of 6MWD measured following PAH treatment retain prognostic power but do not improve on the baseline measurement [144].…”
Section: Field Exercise Testsmentioning
confidence: 94%
“…This was also demonstrable in a meta-analysis of the many treatment trials in PAH [141]. It retains significance in multivariate analyses even when other strong predictors are included such as patient demographics [127,140], baseline haemodynamics from right heart catheterisation or CMR [140,142,143], CPET variables [92,113] and presence of pericardial effusion [127]. Absolute values of 6MWD measured following PAH treatment retain prognostic power but do not improve on the baseline measurement [144].…”
Section: Field Exercise Testsmentioning
confidence: 94%
“…By contributing to the elevated pulmonary vascular resistance, this arteriopathy adversely affects cardiac function and may, in the end, contribute to the progressive hemodynamic instability and increased mortality observed in patients with CTEPH (Riedel et al, 1982). Advanced CTEPH leads to cardiac remodelling, as characterized by right ventricular (RV) dilatation and hypertrophy, tricuspid regurgitation and leftward ventricular septal bowing (LVSB), with a consequent impact on cardiac function (Fleg et al, 2000;Groepenhoff et al, 2008;Kreitner et al, 2007Kreitner et al, , 2004Reesink et al, 2007). We have shown that LVSB is present in the majority of CTEPH patients (Reesink et al, 2007).…”
Section: Pathophysiology Of Ctephmentioning
confidence: 99%
“…For the CPET variables reported by Trip et al, [1] we have provided the survival rates based on cut-off values from previous studies. An oxygen consumption (VO 2 ) <1.32 l/kg/min has cumulative survival rates of 71% [5] and an oxygen (O 2 ) pulse <12 ml/beat with and without cardiopulmonary disease has a relative mortality risk of 3.4 and 2.2, respectively. [6] The reported O 2 pulse of 9.1 ml/beat reported in the current study suggests greater disease severity with a higher mortality risk, which decreased with initiation of treatment, though not completely ameliorating risk.…”
mentioning
confidence: 99%